Accountability in Translation Within and Beyond the Sentence as the Key Functional UT: Three Case Studies - Zhu, Chunshen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe article is a sequel to Zhu (1999). It provides three case studies of translation from English into Chinese, which are designed to substantiate the theoretical framework established therein. It discusses the relationship between a sentence’s internal linear mode of information presentation and its textual potential, the relationship between a sentence’s thematic structure and its functional status in the text, and the necessity and possibility to align sentential speech acts with the textual speech act through appropriate syntactic management. The three case studies, independent as they may seem, are correlated and have been arranged in a progressive order. This article is intended to replace the second part of Zhu (1996a).